2012
DOI: 10.1371/journal.pone.0041525
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Apolipoprotein E Genotype, Diet, Body Mass Index, and Serum Lipids in Lithuanian Adult Population

Abstract: BackgroundApolipoprotein E (APOE) polymorphism is associated with lipid levels. Some studies have reported that blood lipid response to diet or obesity varies depending on APOE genotypes. The aim of this study was to assess the effect of APOE genotypes, the intake of saturated fatty acids (SFA), and obesity on serum lipid levels in Lithuanian adult population.Methodology/Principal FindingsA cross-sectional health survey was carried out in five municipalities of Lithuania. The random sample was obtained from li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 30 publications
3
26
1
1
Order By: Relevance
“…Research data showed that the ApoE polymorphism had a highly significant impact on lipid concentrations (Petkeviciene et al, 2012;Rudkowska et al, 2013). However, environmental factors, including living conditions, diet, and living habits, were also shown to affect blood lipid levels and cerebral infarction (CI) (Egert et al, 2012;Petkeviciene et al, 2012;Rudkowska et al, 2013). Therefore, this study focused on the relationship between the ApoE gene polymorphism and dietary factors in the association with plasma lipid concentrations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research data showed that the ApoE polymorphism had a highly significant impact on lipid concentrations (Petkeviciene et al, 2012;Rudkowska et al, 2013). However, environmental factors, including living conditions, diet, and living habits, were also shown to affect blood lipid levels and cerebral infarction (CI) (Egert et al, 2012;Petkeviciene et al, 2012;Rudkowska et al, 2013). Therefore, this study focused on the relationship between the ApoE gene polymorphism and dietary factors in the association with plasma lipid concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, as the development of molecular biology and genetic engineering technologies has progressed, studies have demonstrated a close association between the ApoE gene polymorphism and serum lipid levels (Shin et al, 2014;Yin et al, 2014;Zhu et al, 2014). It has also been found that dietary factors had some impact on blood lipids, and that this effect could be modified by receptor lipoprotein metabolism (Petkeviciene et al, 2012;Rudkowska et al, 2013). Research data showed that the ApoE polymorphism had a highly significant impact on lipid concentrations (Petkeviciene et al, 2012;Rudkowska et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some human studies have investigated the possible association of variation in this gene with adiposity and/or obesity [11,19,20]. These studies have been conducted in different populations and have shown discrepancies regarding the possible association of ApoE genetic variation and obesity-related traits.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, these data suggest that ApoE may play a role in the development of adiposity. Few human studies have addressed the effect of the genetic variation in this gene on adiposity-related traits, with inconsistent results [8,18,19,20,21]. Thus, the aim of the present study was to analyze the association of the common variation in the ApoE gene, obesity-related traits [BMI, WC, waist-to-height ratio (WHtR) and % body fat] and physical activity in Mexican school children.…”
Section: Introductionmentioning
confidence: 99%